KEPENTINGAN AMERIKA SERIKAT KELUAR DARI TRANS PACIFIC PARTNERSHIP DIMASA PEMERINTAHAN DONALD TRUMP - Anjani, Angga Rizky; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aim to analyze the united state’s interest leaving the Trans Pacific Partnership both political and economic interest on it. Trans Pacific Partnership is a form of free trade agreement comprising 12 countries in the world.The data used in this study is a secondary data. Secondary data was obtained trough library research and search online media research. The writer used behaviourism prepective and individu level of analysis as a references to analyze the motif of united state leave the Trans Pacific Partnership. This study also uses the theory of national interest related to the United State leave the Trans Pacific Partnership.The result of this research is the United State under Donald Trump policy leave thr Trans Pacific Partnership is related to the economy factor which as Donald Trump said Trans Pacific Partnership is tend to threaten the United State Labour and Protectionism is needed for the country in order to achieve the National Interest of United Nation.Keywords: Trans Pacific Partnership, Protecsionism, United Nation Interest